Stellvertretung in Gesundheitsangelegenheiten Modell eines dreigliedrigen Vertretungssystems - Diekmann, Andrea (Universitätsverlag Göttingen, 2009)
A medical measure influences the physical and mental integrity of the affected people. The right of determination is also part of a person's personality. The individual can exercise his right of self determination only when its decision conditions and justifies medical practice. Is an adolescent due to an illness or disability not able to excersise decisions, these have to be made by a representative of legal transactions - an agent - or taken by a legal representative - a supervisor. In this study, the different representation schemes on health matters are presented.